Anthropological analysis of taekwondo - New methodological approach - Cular, D.; Munivrana, G.; Katic, R. (Collegium Antropologicum, 2013)
The aim of this research is to determine the order and importance of impacts of particular anthropological characteristics and technical and tactical competence on success in taekwondo according to opinions of top taekwondo instructors (experts). Partial objectives include analysis of metric characteristics of the measuring instrument, and determining differences between two disciplines (sparring and technical discipline of patterns) and two competition systems (WTF and ITF). In accordance with the aims, the research was conducted on a sample of respondents which consisted of 730 taekwondo instructors from 6 continents and from 69 countries (from which we selected 242 instructors), who are at different success levels in both taekwondo competition systems (styles) and two taekwondo disciplines. The respondents were divided into 3 qualitative subsamples (OST-USP-VRH) using the dependant variable of accomplished results of the instructor. In 6 languages, they electronically evaluated the impact in percentage value (%) of motor and functional skills (MOTFS), morphological characteristics (MORF), psychological profile of an athlete (PSIH), athletic intelligence (INTE) and technical and tactical competence - (TE-TA) on success in taekwondo. The analysis of metric characteristics of the constructed instrument showed a satisfactory degree of agreement (IIr) which is proportional to the level of respondent quality, i.e. it grows along with the increase in instructor quality in all analysed disciplines of both systems. Top instructors assigned the highest portion of impact on success to the motor and functional skills (MOTFS) variable: WTF- -SPB=29.1, ITF-SPB=29.2, WTF-THN=35.0, ITF-THN=32.0). Statistically significant differences in opinions of instructors of different styles and disciplines were not recorded in any of the analysed variables. The only exception is the psychological profile of an athlete variable, which WTF instructors of sparring (AM=23.7%), on a significance level of p<0.01, evaluate as having a statistically significantly higher impact on success in taekwondo than WTF instructors of the technical discipline of patterns (15.4%).